Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1104/pp.16.00295
|View full text |Cite
|
Sign up to set email alerts
|

The Conformation of a Plasma Membrane-Localized Somatic Embryogenesis Receptor Kinase Complex Is Altered by a Potato Aphid-Derived Effector

Abstract: Somatic embryogenesis receptor kinases (SERKs) are transmembrane receptors involved in plant immunity. Tomato (Solanum lycopersicum) carries three SERK members. One of these, SlSERK1, is required for Mi-1.2-mediated resistance to potato aphids (Macrosiphum euphorbiae). Mi-1.2 encodes a coiled-coil nucleotide-binding leucine-rich repeat protein that in addition to potato aphids confers resistance to two additional phloem-feeding insects and to root-knot nematodes (Meloidogyne spp.). How SlSERK1 participates in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…The identification of 6A10 as a large subunit ribosomal RNA of B. tabaci deserves further study. There are many examples of the secretion of effector proteins that modulate plant immunity in saliva from hemipterans including aphids and whitefly Will et al, 2013;Sharma et al, 2014;Su et al, 2015;Peng et al, 2016;Villarroel et al, 2016). For instance, the effector proteins C002, Mp1, and Mp2 from aphid promote fecundity, whereas Mp10 and Mp42 decrease fecundity (Bos et al, 2010;Pitino and Hogenhout, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of 6A10 as a large subunit ribosomal RNA of B. tabaci deserves further study. There are many examples of the secretion of effector proteins that modulate plant immunity in saliva from hemipterans including aphids and whitefly Will et al, 2013;Sharma et al, 2014;Su et al, 2015;Peng et al, 2016;Villarroel et al, 2016). For instance, the effector proteins C002, Mp1, and Mp2 from aphid promote fecundity, whereas Mp10 and Mp42 decrease fecundity (Bos et al, 2010;Pitino and Hogenhout, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Mi-1.2 from tomato encodes a CC-NB-LRR and confers resistance to the potato aphid, the whitefly B. tabaci, the psyllid Bactericerca cockerelli, and the root-knot nematode Meloidogyne incognita, illustrating the first example of a resistance gene acting against distantly related pests Rossi et al, 1998;Nombela et al, 2003;Casteel et al, 2006). In the presence of potato aphid saliva Mi-1.2 was shown to interact with SlSERK1, a receptor kinase related to Arabidopsis BAK1, and this complex formation is suggested to confer aphid resistance (Peng et al, 2016). Vat from melon is also a CC-NB-LRR and, interestingly, provides dual resistance against the aphid Aphis gossypii and viruses transmitted by this vector (Dogimont et al, 2014).…”
Section: Arthropod Resistance Genesmentioning
confidence: 99%
“…There is evidence that herbivore saliva contains factors that can manipulate plant defenses (Will et al, 2013; Sharma et al, 2014; Su et al, 2015; Peng et al, 2016; Villarroel et al, 2016). For hemipterans most knowledge stems from work with aphids: several salivary proteins (effectors) have been identified that affect aphid reproductive rate (Bos et al, 2010; Pitino and Hogenhout, 2013).…”
Section: Introductionmentioning
confidence: 99%